Dinámicas sexuales en la pareja después de la llegada del primer hijo o hija - Torres García, Juliana (Psicología, 2019)
The purpose of this research is identifying the changes in the dynamics of sexual partners after the arrival of the first child, analyzing the implications of the relationship in that area; by analysis of grounded theory and cases. It sought to investigate if the arrival of the first child contributes changes in sexual dynamics of couples who took part in the research